Investigating the morphology and genetics of scalp and facial hair characteristics for phenotype prediction. Issue 1 (January 2023) - Kataria, Suraj; Dabas, Prashita; Saraswathy, K.N.; Sachdeva, M.P.; Jain, Sonal
Highlights: Scalp and facial hair features differ within and among populations. Genetic polymorphisms associated with hair traits may expand our knowledge on human phenotypes. Predicting hair characteristics can improve upon the existing FDP prediction models. Abstract: Microscopic traits and ultrastructure of hair such as cross-sectional shape, pigmentation, curvature, and internal structure help determine the level of variations between and across human populations. Apart from cosmetics and anthropological applications, such as determining species, somatic origin (body area), and biogeographic ancestry, the evidential value of hair has increased with rapid progression in the area of forensic DNA phenotyping (FDP). Individuals differ in the features of their scalp hair (greying, shape, colour, balding, thickness, and density) and facial hair (eyebrow thickness, monobrow, and beard thickness) features. Scalp and facial hair characteristics are genetically controlled and lead to visible inter-individual variations within and among populations of various ethnic origins. Hence, these characteristics can be exploited and made more inclusive in FDP, thereby leading to more comprehensive, accurate, and robust prediction models for forensic purposes. The present article focuses on understanding the genetics of scalp and facial hair characteristics with the goal to develop a more inclusive approach to better understand hair biology by integrating hair microscopy with genetics for genotype-phenotype correlation research.